2010
DOI: 10.3133/ofr20101168
|View full text |Cite
|
Sign up to set email alerts
|

Surface-wave site characterization at 52 strong-motion recording stations affected by the Parkfield, California, M6.0 earthquake of 28 September 2004

Abstract: We present one-dimensional shear-wave velocity (V S) profiles at 52 strong-motion sites that recorded the 28 September 2004 Magnitude 6.0 Parkfield, Calif., earthquake. We estimate the V S profiles with the Spectral Analysis of Surface-Waves (SASW) method. The SASW method is a noninvasive method that indirectly estimates the V S at depth from variations in the Rayleigh wave phase velocity at the surface. To address the uncertainty associated with these measurements, we compare the SASW profiles to surface-sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Kaklamanos et al, 2020;Passeri et al, 2019), only sites with a measured V S profile are used. The measured V S profiles from Japan are provided on the KiK-net database website, whereas various sources are used for the V S profiles of sites in the United States (Afshari et al, 2019;Gibbs et al, 2000;Holzer and Youd, 2007;Thompson et al, 2010;Thornley et al, 2019). A compromise is made to include a few sites with gaps in the V S profile, typically at the top 1-2 m (e.g.…”
Section: Site Characterizationmentioning
confidence: 99%
“…Kaklamanos et al, 2020;Passeri et al, 2019), only sites with a measured V S profile are used. The measured V S profiles from Japan are provided on the KiK-net database website, whereas various sources are used for the V S profiles of sites in the United States (Afshari et al, 2019;Gibbs et al, 2000;Holzer and Youd, 2007;Thompson et al, 2010;Thornley et al, 2019). A compromise is made to include a few sites with gaps in the V S profile, typically at the top 1-2 m (e.g.…”
Section: Site Characterizationmentioning
confidence: 99%
“…The friction angle of the soil is estimated at 40 degrees, and the unit weight of the soil was estimated at 19 kN/m 3 . The shear wave velocity profile is documented in Thompson et al 19 . The foundations for the baseline archetypes (although their foundations were not modeled) and stiff soil archetypes were designed for an allowable bearing pressure of 144 kPa, while the soft soil archetypes were designed for an allowable bearing pressure of 72 kPa.…”
Section: Building Archetypes and Designsmentioning
confidence: 99%
“…The 52 velocity profiles collected by Thompson et al (2010) at strong motion stations are shown in Figure 1. Additionally, we show the epicenter of the 2004 M 6.0 Parkfield earthquake, but we do not include the records from this earthquake in our analysis to avoid the complication of nonlinear and finite fault effects which could be important because epicentral distance to these stations is so small.…”
Section: Data Velocity Profiles and Ground Motion Selectionmentioning
confidence: 99%
“…Of the 52 stations with measured velocity profiles in the Parkfield region, 36 recorded the Coalinga earthquake. Figure 1 also shows the Jennings (1958) Thompson et al (2010) employed the spectral analysis of surface waves (SASW), and so we refer to the V S30 estimated from an SASW V S profile as SASW S V 30 . Additionally, we compute the fundamental site frequency (f 0 ) using the procedure described by Zhao et al, (2006).…”
Section: Data Velocity Profiles and Ground Motion Selectionmentioning
confidence: 99%
See 1 more Smart Citation